THE EFFECTIVENESS OF MINDFULNESS DEEP BREATHING TO INCREASE STUDENTS' ACADEMIC WELL-BEING - Kurnaedi, Nedi; Mutaqin, Moh Fikri Tanzil; Pajriani, Lika (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
The study of positive psychology is currently an interesting part of efforts to form students who are active and happy in the learning process with meaningful activities. Mindfulness deep breathing in the learning process is not widely studied, because research is still limited to individual and group contexts. Thus, this research focuses on the application of classical mindfulness deep breathing format which is effective in improving students' academic well-being. The design used was multiple pretest post test with the research subjects being class X high school students. Data collection uses the Student Subjective Wellbeing Questionnaire (SSWQ). The results of the repeated measure test prove that the classical format mindfulness deep breathing is effective in improving students' academic well-being (f (1,72) = 272,80; p <0,001). The findings in this study show the effectiveness of the mindfulness deep breathing technique implemented in a classical format in improving students' academic well-being.